Respiration rate estimation using non-linear observers in application to wastewater treatment plant. (April 2023) - Czyżniewski, Mateusz; Łangowski, Rafał; Piotrowski, Robert
Abstract: A problem of respiration rate estimation using two new non-linear observers for a wastewater treatment plant is addressed in this paper. In particular, a non-linear adaptive Luenberger-like observer and a super twisting sliding mode observer have been derived to produce stable and bounded estimates of the respiration rate. During the synthesis of the particular observer, an appropriate mathematical utility model was used. The observability analysis of this model was performed using a method of indistinguishable state trajectories. The stability of the devised observers was proved using the Lyapunov stability theory. The performance of the developed observers was validated by simulation using ranges of data from the case study wastewater treatment plant. Satisfactory results have been obtained and they demonstrate high effectiveness of the devised observers. Highlights: Respiration rate estimation problem in a wastewater treatment plant. Synthesis of two new non-linear observers for respiration rate reconstruction. Delivering the proper utility model for observers design purposes. Estimation performance validation by simulation using ranges of real data.